VALIDITY ANALYSIS INTEGRATED BUSINESS MODULES SPATIAL CULTURE-Based PROJECT BEST LEARNING - Rahmattullah; Akmaluddin; Lilis Triana (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research aims to analyze the validity of the entrepreneurship module integrated spatial culture based project best learning. The research was carried out in Banda Aceh City and Greater Aceh District. This research is developmental research. As far as the stages undertaken in this research include the collection of information, data collection, preparation of teaching modules, small-scale trial tests, material development, module preparation, first field trial, revision of the first module, second field test, second module revision, finalisation of the module. This study concluded that the validation from a linguist indicates an excellent level of validation. The validation of a material expert indicates a very good level of validation. The level of practicality of this module could have been tested by two users where the results showed very practical for implementation. The recommendation of this research is the need to implement existing material on the teaching module to cultivate entrepreneurial interest in creating new edupreneurs.